ENGINEERING DESIGN WITH PSO ALGORITHM - MHD BASIR, SITI NUR HAJAR (IRC, 2019)
Currently, engineering design faces multiple complexity as it is very dependent on computer to ensure adequate modelling and simulation optimisation. This creates such problems and one of the root causes is the amount variables used by design engineers. To optimise a mechanical design by the means of distance or even shape, it needs to these handle large numbers of variables, and optimal solution is needed to for such systems. The motive of this dissertation is to utilize Particle Swarm Optimisation (PSO) algorithm on engineering design in the effort of improving design robustness and tolerance with manufacturing. Creating a PSO algorithm-based infrastructure integrating with the recommendation system will further enhance solution to the design problem. It assists design engineers as it gives a clearer visualization to predict which value of the variables gives a best produced result. This dissertation will demonstrate the ability of PSO Algorithm in improving design areas by the use of recommendation system that helps engineering designers to visualise an optimal design.